A three-step metal fractionation scheme for fly ashes collected in an Argentine thermal power plant - Smichowski, Patricia Nora (2008)
A new three-step fractionation scheme was applied to study the distribution of Al, As, Cd, Cr, Cu, Fe, Mn, Mo, Ni, Pb, S, Sb, Ti, V and Zn in fly ashes collected in the electrostatic precipitator of a thermal power plant in the city of San Nicolás (Argentina). Seven samples were collected during one week of operation in 2005. For the fractionation, the scheme applied consisted of extracting the elements in three fractions: (i) soluble and exchangeable elements, (ii) carbonates, oxides and reducible elements and (iii) residual elements. Metals and metalloids at g g-1 level were determined in each fraction by plasma based techniques namely, inductively coupled plasma optical emission spectrometry (ICP OES) and inductively coupled plasma mass spectrometry (ICP-MS). For validation, a certified reference materials NIST SRM 2711 (Montana soil) was subject to the same chemical sequential extraction procedure. X-ray diffraction powder (XRD) analysis and scanning electron microscopy (SEM) were used to characterize the major minerals present in the matrix. The predominant phases found in the total samples were mullite, quartz, iron oxides and lime. Total analyte concentration varied (in g g-1) from 1.54 for Cd to 30600 for Al..The leachability of the 15 elements under study proved to be different. All the elements (except Cd and Pb) were detected in the soluble fraction in the order: Cu (0.10%) ~ Mn (0.13%) < Ni (0.17%) ~ Ti (0.19%) ~ Fe (0.20%) ~ As (0.21%) < Zn (0.86%) < Al (1.3%) < Cr (2.9%) < V (3.9%) < Sb (6.9%) < Mo (45.1%) < S (58.0%). Percentages higher than 20% of S (24.1%) < V (27.5%) < Mn (29.0%) were detected in the second fraction. Al, As, Cr, Cd, Cu, Fe, Ni, Pb, Sb and Zn were mostly associated to the residual fraction. Recoveries of the overall procedure varied between 106% (Mo) and 72% (Cr).